A GIS-based application for volume estimation and spatial distribution analysis of tephra fallout: a case study of the 122 BC Etna eruption - Marina Bisson; Paola Del Carlo (Annals of Geophysics, 2013)
In this study, we demonstrate the use of a geo-spatial information system for volume estimation of fallout deposits and for identification of syn-eruptive and post-eruptive depositional mechanisms. For the first time, we present thickness distribution maps, isopachs maps, and fallout deposit volumes for the single stratigraphic units (A-F) of the 122 BC Plinian eruption of Etna, the most powerful eruption of this volcano in historical times. Thickness data collected during the field survey were organized into a geo-referenced database, and several interpolation algorithms were used to calculate the volumes of the six fallout layers of eruption (units A-F). The results are compared with those obtained using the Pyle method, which bases volume calculations on the exponential thickness-decay law of the deposits. Differences in the two methods are analyzed through applying two-dimensional (2D) and 3D geo-statistical analysis to thickness data, with an 'ideal' fallout deposit used as reference. Our approach allowed both identification of stratigraphic sections where the deposits were affected by secondary erosional or accumulation phenomena, and assessment of whether the secondary processes were caused by local morphologic conditions or by variations in eruptive dynamics (e.g., rotation of dispersal axis direction).